Study on Reducing Drag on Vehicle Side Mirror Via Shape Tuning - Rosman, Ahmad Syakir; Rahmah Mahmudin (Progress in Engineering Application and Technology, 2024)
Side mirrors are crucial components of a car that let the driver see behind and to the side of the vehicle to assess the traffic. However, because of the increased frontal area, side mirrors cause the vehicle’s aerodynamic drag to rise. The goal of the work is to add several forms of flow manipulators to the side-view mirror of the car. Turbulence frequently originates from the erratic flow across side-view mirrors on moving vehicles, which increases drag, noise, and vibration. The use of vortex generators (VGs) to the side-view mirrors of a vehicle is examined using computational fluid dynamics (CFD). To enhance the control surfaces and postpone flow separation, vortex generators are employed, which has an impact on the vehicle’s drag and lift forces. A decrease in drag force may improve fuel efficiency, while an decrease in lift force may enhance vehicle stability and increase vehicle grip force, all of which are crucial for racing automobiles and also quite crucial in normal vehicle. Understanding the VG influence on the flow processes downstream of the side-view mirror, as well as the impact on drag and lift forces, is the main goal of this work. The side-view mirror’s turbulent flow is examined to ascertain the impacts of various VG kinds, geometries, positions, and attack angles.